Information system for the management of scientific production of the University of Medical Sciences of Cienfuegos - Osmel Domingo Medina Martínez; Marle Pérez de Armas; Filiberto Toledo Álvarez; Anay Carrillo Ramos; Raúl Jesús Rosales González; José Antonio Trujillo Arteaga (Medisur)
Foundation: guaranteeing in a timely, reliable and fast manner the information required for the management of scientific production in Cuban Medical Sciences Universities is an outstanding necessity. Objective: to design a computerized information system for the management of scientific production of the University of Medical Sciences of Cienfuegos. Methods: system designed at the University of the Cienfuegos Medical Sciences, based on client-server technology with RUP methodology, UML modeling language, PHP and MySQL programming language as database manager. The minimum requirements are: Dual Core central unit with 2 GB of RAM, 40 GB of hard disk and MySQL and APACHE applications. Results: the system allows the generation of online digital curricula of university professors from any health institution in the province, where their scientific work is highlighted, in addition to the automated calculation of indicators and absolute frequency values at the individual level, career and institution based mainly on parameters of the National Accreditation Board of the Ministry of Higher Education of Cuba. Conclusions: it constitutes a tool that allows perfecting the management of scientific production of Cuban Medical Sciences Universities.